INVESTASI DAN PERTUMBUHAN EKONOMI SUMATERA BARAT - Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
The purpose of the research is to know and analysis causality between invesment and economic growth in West Sumatera. We are using invesment and Economic growth data from 1stquartal 2000 until 4thquartal 2010. We are using unit root test, cointegration test and granger causality test. The result show that investment and economoic growth have causality effect in West Sumatera